Formation of the company's export strategy - Chen Meixia (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the process of developing and implementing an enterprise's export strategy. The subject of research includes scientific-methodological approaches and applied aspects of the formation and functioning of an enterprise's export strategy development. The purpose of the master's thesis is to develop theoretical and methodological provisions and provide recommendations for the formation of an effective export strategy for enterprises under modern conditions. Tasks of a qualifying master's thesis include: to investigate the essential characteristics and peculiarities of forming an enterprise's export strategy; to review and classify strategies for export activities of enterprises; to generalize the methods and models for selecting and justifying an enterprise's export strategy; to provide the technical and economic characteristics of Shekolan LLC; to conduct an analysis of the foreign economic activities of Shekolan LLC; to assess the effectiveness of Shekolan LLC's export activity strategy; to generalize approaches for improving the regulatory mechanisms of Ukraine’s export potential; to propose directions for enhancing the efficiency of export activities at Shekolan LLC; to justify measures for optimizing Shekolan LLC's export strategy. The scientific novelty of the conducted research lies in the development of several theoretical provisions that reveal the economic, organizational, production, and socio-psychological aspects of the development and implementation of an enterprise's export strategy. The study contributes to the theoretical understanding of export strategy formation and provides insights into practical applications tailored to modern economic conditions. The practical significance of the work lies in the formulation of concrete proposals for improving and implementing the export strategy of Shekolan LLC. The findings focus on enhancing the company’s competitive positioning in international markets, streamlining operational processes, and addressing the challenges posed by global market dynamics.
Scientific advisor: Malafeiev T., PhD in public administration, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; strategy; export; enterprise development; competitiveness; foreign economic activity